Quality of Life Changes during the Pre- to Post-Diagnosis Period and Treatment-Related Recovery Time in Older Women with Breast Cancer - Stover, Angela M. (2014)
BACKGROUND: Healthcare providers have little population-based evidence about health-related quality of life (HRQOL) changes, from the pre- to post-diagnosis period, and treatment-related recovery time for women ages 65 and older diagnosed with breast cancer. METHODS: Older women with and without breast cancer completed self-reports of HRQOL at baseline and 2 years later as part of annual Medicare Health Outcomes Surveys (MHOS). MHOS was linked to Surveillance, Epidemiology, and End Results registries, which were used to categorize women with breast cancer by treatment type (breast-conserving surgery, breast-conserving+radiation, mastectomy) and time since diagnosis at follow-up. Each cancer case diagnosed in 1998-2007 (N=542) was matched to five women without cancer (N=2,710) using propensity score matching. Analysis of covariance models examined changes in HRQOL, adjusting for demographics and initial functioning. RESULTS: Older women within 6 months of diagnosis had greater declines than women without cancer in SF-36 Physical (-5.8 vs. -1.8) and Mental (-3.6 vs. -0.7) Component Summary scores, General Health (-12.3 vs. -4.6), Vitality (-11.0 vs. -2.2), Bodily Pain (-8.5 vs. -2.1), Social Functioning (-15.1 vs. -3.3), Role-Physical (-26.5 vs. -3.9), and Role-Emotional (-13.1 vs. -3.1) scores (all p<.05). By approximately 1 year, women with and without breast cancer had similar HRQOL. Comparable declines in Physical Component Summary and Role-Physical occurred across treatment types. CONCLUSION: Women ages 65 and older diagnosed with breast cancer should be counseled that survivors within six months of diagnosis are vulnerable to HRQOL declines, compared to women without breast cancer, but that decrements generally wane after 12 months.